Supporting groups in sorting decisions: Methodology and use of a multi-criteria aggregation/disaggregation DSS - Damart, Sébastien (2007)
This paper addresses the situation where a group wishes to cooperatively develop a common multicriteria evaluation model to sort actions (projects, candidates) into classes. It is based on an aggregation/disaggregation approach for the ELECTRE TRI method, implemented on the Decision Support System IRIS. We provide a methodology in which the group discusses how to sort some exemplary actions (possibly fictitious ones), instead of discussing what values the model parameters should take. This paper shows how IRIS may be used to help the group to iteratively reach an agreement on how to sort one or a few actions at a time, preserving the consistency of these sorting examples both at the individual level and at the collective level. The computation of information that may guide the discussion among the group members is also suggested. We provide an illustrative example and discuss some paths for future research motivated by this work.